2017
DOI: 10.1371/journal.pone.0176937
|View full text |Cite
|
Sign up to set email alerts
|

β-Lapachone suppresses the lung metastasis of melanoma via the MAPK signaling pathway

Abstract: β-Lapachone is a natural quinone compound from Lapacho trees, which has various pharmacological effects such as anti-bacterial, anti-fungal, anti-viral, and anti-inflammatory activities. However, the effect of β-lapachone on metastasis of melanoma cells is unclear. In this study, β-lapachone reduced cell viability of metastatic melanoma cancer cell lines B16F10 and B16BL6 through induction of apoptosis via the mitogen-activated protein kinase (MAPK) pathway. Additionally, flow cytometry results showed that β-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
11
0
3
Order By: Relevance
“…The metastatic spread of the primary lesion is the worst scenario when dealing with melanoma. In fact, melanoma is the most aggressive skin malignancy, giving rise to lung and brain metastasis in most of the patients suffering from distant lesions [ 29 , 30 ]. To study the antitumor effect of Ocoxin, we analyzed the lung metastasis of YUMM-1.7 melanoma upon different treatment routines.…”
Section: Resultsmentioning
confidence: 99%
“…The metastatic spread of the primary lesion is the worst scenario when dealing with melanoma. In fact, melanoma is the most aggressive skin malignancy, giving rise to lung and brain metastasis in most of the patients suffering from distant lesions [ 29 , 30 ]. To study the antitumor effect of Ocoxin, we analyzed the lung metastasis of YUMM-1.7 melanoma upon different treatment routines.…”
Section: Resultsmentioning
confidence: 99%
“…Murine Bl6-F10 cells were established from lung metastasis of B16-F0 cells by i.v. injection through 10 successive selections and are usually employed to investigate the anti-metastatic effects of different compounds (Fidler, 1973;Mummert et al, 2003;Chien et al, 2015;Kee et al, 2017). The interaction of melanoma cells with extracellular matrix proteins is one of the initial steps crucial for metastatic dissemination and we found that TAP7f inhibited cell adhesion to the immobilized matrix proteins vitronectin and fibronectin.…”
Section: Discussionmentioning
confidence: 65%
“…Thus, PEITC and BITC may affect cell migration and invasion of A375.S2 cells via MAPK pathway. MAPK pathway regulated cellular invasion and metastasis (49) and suppression of MAPK pathway could prevent cancer's invasion and metastasis including in melanoma (50,51).…”
Section: Discussionmentioning
confidence: 99%